Role of spirituality and sense of coherence as protective factors against work burnout among palliative care volunteers - Ruszkiewicz, Marta; Eldridge, Ewa (Psychoonkologia, 2015)
Introduction : Performing tasks connected with delivering psychological help and support is usually perceived as a social mission. Providing support for those facing difficult life situations, especially for people facing life threatening disease, can clearly be the source of tremendous satisfaction and pride. The significance of such support and the intense feelings engendered may rarely be found in other occupations. Despite the highly positive aspects of this work, there is evidence that this occupation can also be a threat to the psychological wellbeing of those undertaking such work. Long term exposure to the stressors prevalent in this profession can give rise to serious issues which in turn can lead to burnout. Numerous studies in this field show that an increasing number of professionals performing tasks connected with psychological care of the chronically ill are exposed to the risk of burnout. This effect includes both groups of psychological care professionals – those who are paid for their work as well as volunteers. Therefore, recognition of the burnout protective measures becomes crucial. The aim of following study was to verify whether personal resources such as sense of coherence and spirituality may perform such a role. Material and methods : The study has been conducted on a group of 44 palliative care volunteers who were given Sense of Coherence Scale (SOC-29), KS questionnaire and Maslach Burnout Inventory (MBI). Results and conclusions : The results confirm that spirituality and sense of coherence can act as protective factors in one dimension of burnout i.e. Personal Accomplishment.